Study and analysis of novel RF MEMS switched capacitor - Vikas, K; Sunithamani, S; Yagnika, M; Siva Krishna, S; Avanthi, S (International Journal of Engineering and Technology, 2018)
In this paper we have designed and analyzed shunt capacitive fixed-fixed RF MEMS switch to maintain low actuation voltage. The pull - in voltage of the proposed switch is 7.7V for 2 um air gap. The electromagnetic analysis for the designed structure is, return loss is -23dB in the range of 1-40 GHz, insertion loss is -0.04dB at a frequency range of 1-40 GHz and isolation is - 38.5dB obtained at a frequency of 23.5 GHz. Mechanical analysis for the designed structure is also performed using FEM tool.